The Secreted Effector Protein EspZ Is Essential for Virulence of Rabbit Enteropathogenic Escherichia coli - Wilbur, John Scott (Infect Immun, 2015)
Attaching and effacing (A/E) pathogens adhere intimately to intestinal enterocytes and efface brush border microvilli. A key virulence strategy of A/E pathogens is the type III secretion system (T3SS)-mediated delivery of effector proteins into host cells. The secreted protein EspZ is postulated to promote enterocyte survival by regulating the T3SS and/or by modulating epithelial signaling pathways. To explore the role of EspZ in A/E pathogen virulence, we generated an isogenic espZ deletion strain (ΔespZ) and corresponding cis-complemented derivatives of rabbit enteropathogenic Escherichia coli and compared their abilities to regulate the T3SS and influence host cell survival in vitro. For virulence studies, rabbits infected with these strains were monitored for bacterial colonization, clinical signs, and intestinal tissue alterations. Consistent with data from previous reports, espZ-transfected epithelial cells were refractory to infection-dependent effector translocation. Also, the ΔespZ strain induced greater host cell death than did the parent and complemented strains. In rabbit infections, fecal ΔespZ strain levels were 10-fold lower than those of the parent strain at 1 day postinfection, while the complemented strain was recovered at intermediate levels. In contrast to the parent and complemented mutants, ΔespZ mutant fecal carriage progressively decreased on subsequent days. ΔespZ mutant-infected animals gained weight steadily over the infection period, failed to show characteristic disease symptoms, and displayed minimal infection-induced histological alterations. Terminal deoxynucleotidyltransferase-mediated dUTP-biotin nick end labeling (TUNEL) staining of intestinal sections revealed increased epithelial cell apoptosis on day 1 after infection with the ΔespZ strain compared to animals infected with the parent or complemented strains. Thus, EspZ-dependent host cell cytoprotection likely prevents epithelial cell death and sloughing and thereby promotes bacterial colonization.